PENINGKATAN HASIL BELAJAR MAHASISWA PGSD UN PGRI KEDIRI DENGAN MODUL BERBASIS KONFLIK KOGNITIF PADA MATERI MENYUSUN PERANGKAT PEMBELAJARAN IPA SD - Rachmawati, Linda; Mukmin, Bagus Amirul (JURNAL PENDIDIKAN DASAR NUSANTARA, 2018)
In science lesson of elementary school, there are some problems related to the students' learning outcomes that are still low. This is proved by the average score of students is 69 and viewed from the percentage of students' learning achievement is 38%. This is because the students understanding related to the preparation of teaching administrations are still lack. Another factor that influences is lecturer teaching method is not appropriate. The learning that is applied so far is teacher-centered, so that students are more passive and less involved in learning activity. The objective of this study is to improve the students learning outcomes of science lesson of elementary school. This research used classroom action research with the stages of planning, implementation, observation, and reflection. This research subjects are A class of 6th semester of Primary School Teacher Education Department, Nusantara PGRI Kediri University. The data of this study are collected by observation and test techniques. The results showed that the average increase in student learning outcomes from pre-cycle activities of 69, in the first cycle 73, and on the second cycle increased to 83. While the percentage of students' learning achievement also increased from pre-cycle activity by 38%, in the first cycle to 59%, and in second cycle reached 87%. Based on the results study, it can be concluded that the module based on cognitive conflict can improve the understanding and learning outcomes of students in Science Lesson of Elementary School of Primary School Teacher Education Department, Nusantara PGRI Kediri University. Keywords: learning outcomes, module based on cognitive conflict.